miR-1 Inhibits the Ferroptosis of Chondrocyte by Targeting CX43 and Alleviates Osteoarthritis Progression - Ming Zhou; Chenjun Zhai; Kai Shen; Gang Liu; Lei Liu; Jian He; Jun Chen; Yaozeng Xu (Journal of Immunology Research, 2023)
Dysregulation of miRNAs in chondrocytes has been confirmed to participate in osteoarthritis (OA) progression. Previous study has screen out several key miRNAs may play crucial role in OA based on bioinformatic analysis. Herein, we identified the downregulation of miR-1 in OA samples and inflamed chondrocytes. The further experiments revealed that miR-1 played an essential role in maintaining chondrocytes proliferation, migration, antiapoptosis, and anabolism. Connexin 43 (CX43) was further predicted and confirmed to be the target of miR-1, and mediated the promotion effects of miR-1 in regulating chondrocyte functions. Mechanistically, miR-1 maintained the expression of GPX4 and SLC7A11 by targeting CX43, attenuated the accumulation of intracellular ROS, lipid ROS, MDA, and Fe2+ in chondrocytes, thereby inhibiting the ferroptosis of chondrocytes. Finally, experimental OA model was constructed by anterior cruciate ligament transection surgery, and Agomir-1 was injected into the joint cavity of mice to assess the protective effect of miR-1 in OA progression. Histological staining, immunofluorescence staining and Osteoarthritis Research Society International score revealed that miR-1 could alleviate the OA progression. Therefore, our study elucidated the mechanism of miR-1 in OA in detail and provided a new insight for the treatment of OA.